Imperfect preventive maintenance for numerical control machine tools with log-linear virtual age process - Guo, Jun-feng; Rui, Zhi-yuan; Feng, Rui-cheng; Wei, Xing-chun (Journal of Central South University, 2014)
Based on the log-linear virtual age process, an imperfect preventive maintenance policy for numerical control (NC) machine tools with random maintenance quality is proposed. The proposed model is a combination of the Kijima type virtual age model and the failure intensity adjustment model. Maintenance intervals of the proposed hybrid model are derived when the failure intensity increase factor and the restoration factor are both random variables with uniform distribution. The optimal maintenance policy in infinite time horizon is presented. A numerical example is given when the failures of NC machine tools are described by the log-linear process. Finally, a discussion is presented to show how the optimal results depend on the different cost parameters.